Whey Fortified Ready-to-Reconstitute Elephant Apple (Dillenia Indica) Juice Powder: Methodical Optimization, Micro-Structural and in Vitro Digestion Analyses - Borah, Udangshree; Boruah, Rimki; Islam, Sahijul; Borah, Abhijit; Saikia, Ananta; Boro, Robin; Saikia, Hemanta; Mutnuri, Srikanth; Ganguly, Anasuya; Baishya, Rinku; Saikia, Lakshi; Purkayastha, Manashi Das (Journal of Food Technology Research, 2022)
Elephant apple fruit, though bestowed with multifarious medicinal properties and available in many Asian countries, has no known commercial processed product due to its tough fibrous calyces, highly astringent juice and brown discolouration. In this study, the juice was blended with concentrated whey in different proportions (v/v) for assessing organoleptic acceptability. Principal Component Analysis of the sensory scores and subsequent evaluation of blends’ antioxidant activity revealed the superiority of 1:1 (v/v) admixture over other counterparts. Further, study focussed on optimization of process variables (maltodextrin concentration and inlet temperature of spray dryer) for recuperating beverage powder from the juice-whey blend (1:1 v/v). Developed powders presented different surface morphologies (wrinkled/shrunk/ellipsoidal/fused particles having 2-30 µm diameters), and were organoleptically favourable with good yield (63.33-88.33%), dispersibility (33.40-56.57%), moderate antioxidative potential (37.45-54.57%), improved sugar, protein and whiteness index. In-vitro digestion release of protein and antioxidant activity from the optimized powder showed increasing trend with time, unlike those of fresh juice and juice-whey blend (1:1 v/v). Thus, ready-to-reconstitute juice powder(s) with appreciable features was developed from an underutilized fruit using methodical statistical approaches, and the resultant product was found to provide protracted release of protein and antioxidants during simulated digestion.